Influence of irrigation with microalgae-treated biogas slurry on agronomic trait, nutritional quality, oxidation resistance, and nitrate and heavy metal residues in Chinese cabbage. (15th August 2019) - Xu, Zhi-Min; Wang, Zhen; Gao, Qiong; Wang, Li-Li; Chen, Li-Li; Li, Qiao-Guang; Jiang, Jian-Jun; Ye, Han-Jie; Wang, Dong-Sheng; Yang, Ping
Abstract: Biogas slurry (BS) is a main byproduct of biogas production that is commonly used for agricultural irrigation because of its abundant nutrients and microelements. However, direct application of BS may cause quality decline and nitrate and heavy metal accumulation in crops. To address this issue, a microalgae culture experiment and an irrigation experiment were performed to evaluate the removal efficiencies of nutrients and heavy metals from diluted BS by microalgae Scenedesmus sp. and to investigate the effects of irrigation with microalgae-treated BS (MBS-25, MBS-50, MBS-75, and MBS-100) on nutritional quality, oxidation resistance, and nitrate and heavy metal residues in Chinese cabbage. After 8 days of continuous culture, a ratio of 1/1 for BS/tap water mixture (BS-50) was the optimal proportion for microalgal growth (3.73 g dry cell L −1 ) and efficient removal of total nitrogen (86.1%), total phosphorus (94.3%), COD (87.5%), Cr (50%), Pb (60.7%), and Cd (59.7%). The pH in MBS-50 medium recovered to the highest level in a shorter period of time and accelerated the gas stripping of ammonia nitrogen and the formation of insoluble phosphate and metals, which partly contributed to the high removal efficiencies. MBS irrigation significantly promoted crop growth; improved nutritional quality, edible taste, and oxidation resistance; and reduced nitrate and heavy metal residues in Chinese cabbage at a large scale. Therefore, microalgae culture was beneficial to reduce negative impacts of BS irrigation in crop growth and agricultural product safety. This study may provide a theoretical basis for the safe utilization of BS waste in agricultural irrigation. Highlights: Tap water as diluent reduced the cost of BS treatment and Scenedesmus sp. culture. The BS: tap water of 1:1 achieved the best microalgae growth and pollution removal. MBS irrigation improved crop yield, nutritional quality, and oxidation resistance. MBS irrigation reduced consumption risks of nitrate and heavy metal accumulation.